The Sport Engagement Scale: An Adaptation of the Utrecht Work Engagement Scale (UWES) for the Sports Environment - Guillén, Félix; Universidad de Las Palmas de Gran Canaria (2014)
The Utrecht Work Engagement Scale (UWES) is an instrument designed by Schaufeli y Bakker (2003) to measure engagement in the work context. The purpose of the present study is to adapt the UWES to the sports context. The sample consists of 240 national third division Spanish football players between the ages of 15 and 38. The UWES factor structure has been analyzed through exploratory and confirmatory factor analyses. The results reveal a three-factor structure of the scale (vigor, absorption and dedication) and also an adequate internal consistency in all cases. Finally the results show preliminary support for the validity of the construct as sport burnout is negatively related to the three engagement characteristics. These findings provide preliminary evidence for the benefits of using the UWES in the sports context.